2004
DOI: 10.1111/j.1440-1827.2004.01596.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of centromere protein F expression in buccal and gingival squamous cell carcinoma

Abstract: Centromere protein F (CENP-F) expression (localization and characteristics) in relation to tumor clinicopathological parameters was immunohistochemically examined and evaluated in 47 archival biopsy specimens of buccal and gingival squamous cell carcinomas (SCC). Centromere protein F expression was detected in 79% of the samples. An increase in the labeling index (LI) with WHO grading was obtained (P < 0.05). Correlations were obtained between the CENP-F LI and tumor size (P < 0.05). Immunoelectron microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
(35 reference statements)
2
3
0
1
Order By: Relevance
“…In our study, the positive nuclei of CENP-F were diffusely distributed over tumour tissues, which is not completely in line with other reports in which positive nuclei were mainly detected in the tumour front of buccal and gingival squamous cell carcinomas 24. In addition, both cytoplasmic and nuclear staining of CENP-F was detected.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our study, the positive nuclei of CENP-F were diffusely distributed over tumour tissues, which is not completely in line with other reports in which positive nuclei were mainly detected in the tumour front of buccal and gingival squamous cell carcinomas 24. In addition, both cytoplasmic and nuclear staining of CENP-F was detected.…”
Section: Discussionsupporting
confidence: 81%
“…Otherwise, the specimen was defined as negative. The labelling index (LI) was determined by the summation of the percentage of positive-staining nuclei or cells (PP) and the staining intensity (SI), which were adapted from the definitions reported by Esguerra et al 24. The percentage of positive-staining cells (PP) was scored in the following manner: 0 (negative), 1 (<20%), 2 (20–50%) and 3 (>50%).…”
Section: Methodsmentioning
confidence: 99%
“…CENP-F plays a significant role in kinetochore assembly and the spindle checkpoint. Esguerra et al reported a correlation between the expression of CENP-F and the Ki-67 labeling index in oral SCCs (24). We have also reported that CENP-F mRNA levels were higher in patients with oral SCCs harboring lymph node metastasis than in cases without metastasis (25).…”
Section: Discussionsupporting
confidence: 68%
“…The expression of CENP-F in malignancies has been investigated over the past decade, with increased immunohistochemical expression of CENP-F reported in breast, lung, ovarian and cervical cancer, non-Hodgkin lymphoma as well as squamous cell carcinoma of the oesophagus, oral mucosa and gingiva [ 7 , 11 ]. Elevated expression of CENP-F has prognostic implications, correlating with clinical and pathological parameters of poor prognosis in primary breast cancer including higher standardised uptake values on positron emission tomography (PET) scan, shorter disease free survival times and higher recurrence rates [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%